Using proteomic technologies to understand the impact of stress and nutritional factors on fish metabolism, welfare and quality - Silva, Tomé Pereira de Azevedo (2015)
As the scale of aquacultural activities increases, we increasingly face challenges, not only in terms of sustainability, but also regarding issues like animal welfare and product quality. Within these research fields, proteomics (along with other -omics) is establishing itself as an invaluable tool for an untargeted assessment of the impact of exogenous stimuli on fish metabolism. This dissertation describes work developed in this area, where proteomic technologies were used to understand the impact of stress and nutritional factors on fish metabolism, welfare and quality. Gilthead seabream was chosen as the main biological model, due to its high importance in the Portuguese aquaculture sector, with Senegalese sole as secondary model. These studies were focused on both skeletal muscle and liver tissue. Results demonstrated that a reproducible proteomic analysis of the sarcoplasmic fraction of gilthead seabream muscle is feasible, with pre-slaughter stress inducing a clear hastening of the transition between the pre-rigor and post-rigor profiles. Comparatively, glycerol supplementation (as a tool to modulate muscle glycogen reserves) was shown to have a more subtle impact on the sarcoplasmic proteome of gilthead seabream, with results generally suggesting adaptive effects associated with this dietary factor. Hepatic proteome analyses revealed a high sensitivity towards both stress and dietary factors, with stress factors again displaying a broader impact on protein expression. In these experiments, the proteomic responses to sources of stress displayed specificities that depend on both the biological model and the type/duration of stressor, despite some degree of overlap in terms of the affected pathways. Concluding, despite the apparent resilience of gilthead seabream quality attributes in regards to nutritional and/or stress factors, proteome analysis revealed that these factors have an impact on both muscle and liver metabolism, being likely to affect post-mortem muscle degradation dynamics. The suggestion of specific candidates for further targeted studies underlines the usefulness of proteomics in this context.